Tinjauan Teologis dan Spiritualitas Kristiani atas Peran Kaum Muda sebagai Masa Kini Gereja menurut Christus Vivit - Rikha Emyya Gurusinga; Regina Dipa Gurusinga (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2025)
The purpose of this research is to analyze the role of young people as an integral and active part of contemporary church life based on theological approaches and Christian spirituality in the light of the apostolic document Christus Vivit by Pope Francis. This research uses a library research method with primary data in the form of Catholic Church documents, especially Christus Vivit, as well as relevant theological and pastoral references. The analysis technique is done through textual study and theological reflection. The results of the study show that young people are seen as subjects of the Church today who have great potential in realizing spiritual and pastoral renewal. Their spirituality is shaped by a personal relationship with the living Christ, active involvement in the community, and a missionary spirit. The findings confirm that the Church needs to open a wider space for the involvement of young people as part of the dynamics of evangelization in the midst of the challenges of the times.